Peran Madrasah Diniyah Awaliyah (MDA) Masjid Al-Falah Dalam Talang Empat Kabupaten Bengkulu Tengah - Sohib, Syahrul Muhammad; Putri, Meistika Padliana; Aini, Nurul; Anggara, Pebi Djali; Almunawaroh, Istiqomah; Ardhi, Pitriyani, Bayan; Herawati, Tika; Abzis, Afriami (Pakis Journal Institute, 2024)
This article is the result of the implementation of the Real Work Lecture (KKN) for Class III students by UIN Fatmawati Soekarno Bengkulu. The activity aims to educate the public on the role of religious schools Madrasah Diniyah Awaliyah (MDA) in the moral development of children. MDA need good leadership, especially in the formation of children's morality. As part of the implementation process, MDA carry out activities related to recitation, namely learning to read, write and recite the Holy Quran through a curriculum developed by the Ministry of Religion and implemented according to existing conditions. In addition to this, MDA Al-Falah Mosque also instills religious values related to character in the children of MDA, namely religious character, honesty, discipline, curiosity, creativity and responsibility. This character development is an important part of the MDA program at Al-Falah Mosque, located in Al Sebakul Village, Talang Enpat, Central Bengkulu District.